ANALISIS MEMBACA PERMULAAN SISWA KELAS II DI SDN 01 ANJONGAN - Murjanah (STKIP Subang, 2025)
This study study aims to analyze the initial reading skills of second-grade students at SDN 01 Anjongan, especially in the aspects of recognizing letters, combining syllables, and understanding simple meanings. This study uses a descriptive qualitative approach, with the research subjects being second-grade students of SDN 01 Anjongan in the 2024/2025 academic year. Data collection techniques were carried out through observation, interviews, and initial reading tests (EGRA). The results of the study showed that some students still had difficulty recognizing certain letters, especially letters that have similar shapes such as b-d and p-q, as well as in pronouncing the letters X and Y. In addition, it was also found that some students had difficulty combining syllables into whole words, as well as reading fluently and understanding the contents of simple readings. Factors causing these difficulties include lack of reading practice at home, learning methods that have not been varied, and a less supportive learning environment. Based on these results, teachers are advised to use interesting and interactive learning media, such as letter cards, phonetic games, and shared reading, in order to improve students' initial reading skills